In silico analyses of the human sperm‐specific antigen 2 and its role in oral squamous cell carcinoma. Issue 1 (25th February 2022) - Khowal, Sapna; Wajid, Saima
Abstract: Oral cancer is a serious threat to humans worldwide. The frequently diagnosed form of oral cancer is oral squamous cell carcinoma (OSCC). The major etiologies of OSCC are the chemical constituents/carcinogens found in tobacco, areca nut, and alcohol. The sperm‐specific antigen 2 ( SSFA2 ) is a crucial human gene and encodes for a protein that communicates between InsP3Rs and the cytoskeleton, regulating the cellular molecular pathways. This study analyzed the role of SSFA2 in OSCC using a computational approach. First, the evolutionarily conserved attributes of human SSFA2 canonical protein (HSCP) were scrutinized, followed by its comparison with human SSFA2 noncanonical proteins (HSNCPs); in addition, the transcript variants encoding for HSCP and HSNCP were also analyzed for sequence disparities. Molecular docking (iGEMDOCK) was performed for predicting HSCP residues interacting with OSCC carcinogens and OSCC therapeutants. Further, the protein interactome of HSCP was analyzed using Cytoscape. >70% amino acids (AAs) in HSCP were evolutionarily conserved; the AAs in the N‐terminal and C‐terminal regions were more conserved than that in the middle region of the protein. The 12 transcript and protein variants encoded by the human SSFA2 showed substantial differences in their sequences. Additionally, the human SSFA2 protein variants showed disparities in their secondary and tertiary structures. Molecular docking showed favorable interaction of carcinogens and therapeutants with the N‐terminus, middle region, and C‐terminus residues of HSCP, highlighting its strong candidature as the therapeutic target in oral malignancy. The structure and protein interactome analyses of HSCP predicted its diverse functionalities in the cell environment. Also, the sequence and structure heterogeneity present between HSCP and HSNCPs implies their varying functional attributes/roles in normal and/or diseased physiologies. Abstract : Oral squamous cell carcinoma (OSCC) is caused by the chemical constituents of tobacco, areca nut, and alcohol. The sperm‐specific antigen 2 ( SSFA2 ) is a crucial human gene and the encoded protein communicates between InsP3Rs and the cytoskeleton, regulating the associated cellular molecular pathways. This study analyzed the role of SSFA2 in OSCC using the computational approach.